Insights into the surface chemistry and electronic properties of sp2 and sp3-hybridized nanocarbon materials for catalysis. Issue 35 (18th April 2017) - Lin, Yangming; Feng, Zhenbao; Yu, Linhui; Gu, Qinging; Wu, Shuchang; Su, Dang Sheng
Abstract : Compared with other carbon materials, the surface chemistry, electronic properties and corresponding catalytic performance of nanodiamond and its derivatives are investigated. Abstract : Ultra-dispersed nanodiamond and its derivatives (UNDDs), including bucky nanodiamond and onion-like carbon, offer superior catalytic behavior relative to other nanocarbons. However, a systematic study of their unique properties has been rarely achieved. Their surface chemistry and electronic properties are therefore studied to reveal the essential differences of UNDDs compared to other nanocarbons for catalysis.